Analisa Perumusan Konsep Ketuhanan Menurut Perspektif Thomas Beighton (1790-1844) Dalam Karya Inilah Kunci Pengempar (1841): Analysis of the Formulation of the Concept of Divinity from Thomas Beighton’s (1790-1844) Perspective in the Work Inilah Kunci Pengempar (1841) - Ngadiran, Siti Nor Aisyah; Denisova, Tatiana A. (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Writing and printing are among the fields pioneered by the London Missionary Society (LMS) missionaries since their arrival in the Straits Settlements at the beginning of the 19th century AD. Thomas Beighton (1790-1844) was involved in this role, particularly within the Malay Muslim community of Penang. This required from Beighton, a mastery of the Malay language and Jawi script, which enabled him to produce a large number of works in that language. Therefore, this study which uses textual content analysis will concentrate on one of Beighton’s works dealing with the concept of divinity entitled, Inilah Kunci Pengempar (This is the Centrifugal’s Key), published in Penang in 1841. Through this work, Beighton has used a metaphysical approach in his writing to spread Christianity in the country. As a result, Beighton was discovered attempting to apply the concept of divinity based on the concept of trinity, which refers to God: the Father (Allah), Son of God (Jesus), and the Holy Spirit in all descriptions. This shows the efforts of the Christian missionaries at that time, who were enthusiastic about spreading the religion, including learning Arabic and comprehending certain concepts in both divine matters and Islamic law (the Shari‘ah).